Aspects of the breeding biology of antarctic petrels and southern fulmars in the rauer group, east Antarctica - FI Norman; MD Whitehead; SJ Ward; John Arnould (1992)
Breeding phenology, success and nest attendance of Antarctic Petrels Thalassoica antarctica and Southern Fulmars Fulmarus glacialoides at the Rauer Group (68°51'S, 77°50'E), East Antarctica, are discussed. Most data were collected on Hop Island (68°50'S, 77°42'E) in January and February 1988, and from December 1988 to March 1989. Observations extended from the late stages of incubation to post-guard or fledging periods. Some annual breeding indices collected from 1983 onwards at census sites are compared with meteorological data and the extent of fast ice for the nearby Davis Station (68°35'S, 77°58'E). Both species had a restricted hatching period, reflecting a brief and synchronised egg-laying period, typical of other southern fulmarine petrels. Antarctic Petrel chicks hatched from 4 January (1989), and c. 90% appeared by 16 January (both years). Southern Fulmar hatching began on 21 January (1988) and almost all chicks appeared by 6 February (both years). Adult attendance at nests declined with increasing chick age. For Antarctic Petrels, this was most marked at about 11 days; no chicks had continuously attendant adults after 24 days, although adults returned to feed them. Incubation shifts in Southern Fulmars were longer than shifts following hatching and the post-guard period started, on average, 13 days after hatching. Egg and chick losses varied between years and sites. The South Polar Skua Catharacta maccormicki was apparently involved in the majority of losses. Nest sites of both species resemble those elsewhere: Southern Fulmars may require steeper sites, allowing a fall away from colonies. Antarctic Petrels are less affected by accumulation of snow or ice and shelter from katabatic winds may be important. Although weather may modify breeding success locally, annual success must depend on the ability of parents to produce eggs and feed chicks: this may be moderated by the extent and persistence of pack ice.